2007
DOI: 10.1007/s00439-007-0449-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation study of the H37/RBM5 tumor suppressor gene from the 3p21.3 human lung cancer tumor suppressor locus

Abstract: Loss of heterozygosity (LOH) at chromosome 3p21.3 is one of the most prevalent genetic disturbances occurring at the earliest stage of tumor development for a wide variety of human cancers, culminated in lung cancer. The 19 genes residing at 3p21.3 have been vigorously characterized for tumor suppressor activity and gene inactivation mechanism because of their potentially significant merits of clinical applications. Many of these 19 genes have been shown to manifest various growth inhibitory properties, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(95 citation statements)
references
References 29 publications
6
89
0
Order By: Relevance
“…Consistently, H37 triggers mitochondrial apoptotic pathways downstream of Bax, in a p53-independent manner, which include breakdown in the mitochondrial membrane potential, cytochrome c release into cytosol, and enhanced caspase-9 and caspase-3 activities [11]. Further, as compared with adjacent normal tissue, our findings show reduced expression in primary lung cancers of H37 transcript and protein in 9 of 11 (82%) and 46 of 62 (73%) samples, respectively [12], although the H37/3p21.3 LOH genomic status for these samples was unknown. The involvement of H37 in malignancy has been also reported by other investigators for a variety of cancer types.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Consistently, H37 triggers mitochondrial apoptotic pathways downstream of Bax, in a p53-independent manner, which include breakdown in the mitochondrial membrane potential, cytochrome c release into cytosol, and enhanced caspase-9 and caspase-3 activities [11]. Further, as compared with adjacent normal tissue, our findings show reduced expression in primary lung cancers of H37 transcript and protein in 9 of 11 (82%) and 46 of 62 (73%) samples, respectively [12], although the H37/3p21.3 LOH genomic status for these samples was unknown. The involvement of H37 in malignancy has been also reported by other investigators for a variety of cancer types.…”
Section: Introductionsupporting
confidence: 78%
“…Briefly, 5 μg of total RNA was primed with 500 ng of oligo(dT) [12][13][14][15][16][17][18] in a total of 12 μl reaction volume for 10 min. at 70°C followed by quick chill on ice.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Previous studies suggest that frequently reduced RBM5 levels exist in different types of tumors including breast cancer (25), schwannoma (26), and ~75% of primary lung cancers (27). We previously reported that the protein levels of RBM5 are lower in NSCLC compared with non-tumorous tissues (13).…”
Section: Discussionmentioning
confidence: 85%
“…Loss of heterozygosity at this locus occurs in 95% of small-cell lung cancer (SCLC), as well as 70% of non-SCLC (Sutherland et al 2010). Consistent with a role as a tumor suppressor, RBM5 (also known as LUCA-15 and H37) was later shown to be down-regulated in a high proportion of lung cancers (Oh et al 2002). RBM5 was also one of nine genes down-regulated as part of a ''metastatic signature'' identified by microarray (Ramaswamy et al 2003).…”
Section: Rna-binding Motif 5 (Rbm5)mentioning
confidence: 96%